The Impact of Global Budgets on Pharmaceutical Spending and Utilization: Early Experience From the Alternative Quality Contract. (1st December 2014) - Afendulis, Christopher C.; Fendrick, A. Mark; Song, Zirui; Landon, Bruce E.; Safran, Dana Gelb; Mechanic, Robert E.; Chernew, Michael E.
In 2009, Blue Cross Blue Shield of Massachusetts implemented a global budget-based payment system, the Alternative Quality Contract (AQC), in which provider groups assumed accountability for spending. We investigate the impact of global budgets on the utilization of prescription drugs and related expenditures. Our analyses indicate no statistically significant evidence that the AQC reduced the use of drugs. Although the impact may change over time, early evidence suggests that it is premature to conclude that global budget systems may reduce access to medications.